Gestión del mantenimiento automotriz: Un acercamiento al mantenimiento preventivo 4.0 y los carros conectados (2020)
The fourth industrial revolution integrates the Internet of everything into the value chain of a process, joining products with its environment through the intelligent management of data analytics, along with the computational capacity to build cyberspace. The union between the physical world and the virtual world happens in the cyber physical systems, which are used to distribute, monitor, control physical environments and generate feedbacks. The car must be understood as a cyber physical system, because it must incorporate intelligent elements and must be connected through the internet to share information on its state and to give real time responses of the performance of the car to its owner, building the Connected cars concept. With the data obtained in real time of the vehicle, a data treatment is done from the point of view of maintenance. Firstly, it is necessary to know the origin of the data, along with its status. Once these information is defined, a technical and promotional analysis assisted by big data analytics is carried out, leading to a professional and autonomous control of the intelligent device over the monitored element and the use of data to improve the automotive maintenance shop management